NOD/SCID IL2Rγ-null mouse xenograft model of human p53-mutated chronic lymphocytic leukemia and ATM-mutated mantle cell lymphoma using permanent cell lines - Verner, Jan; Trbusek, Martin; Chovancova, Jana; Jaskova, Zuzana; Moulis, Mojmir; Folber, Frantisek; Halouzka, Roman; Mayer, Jiri; Pospisilova, Sarka; Doubek, Michael (Leukemia & lymphoma, 2015)
Xenograft models represent a promising tool to study the pathogenesis of hematological malignancies. To establish a reliable and appropriate in vivo model of aggressive human B-cell leukemia and lymphoma we xenotransplanted four p53-mutated cell lines and one ATM-mutated cell line into immunodeficient NOD/SCID IL2Rγ-null mice. The cell lines MEC-1, SU-DHL-4, JEKO-1, REC-1, and GRANTA-519 were transplanted intraperitoneally or subcutaneously and the engraftment was investigated using immunohistochemistry and flow cytometry. We found significant differences in engraftment efficiency. MEC-1, JEKO-1 and GRANTA-519 cell lines engrafted most efficiently, while SU-DHL-4 cells did not engraft at all. MEC-1 and GRANTA-519 massively infiltrated organs and the whole intraperitoneal cavity showing very aggressive growth. In addition, GRANTA-519 cells massively migrated to the bone marrow regardless of the transplantation route. The MEC-1 and GRANTA-519 cells can be especially recommended for in vivo study of p53-mutated chronic lymphocytic leukemia and ATM-mutated mantle cell lymphoma, respectively.
Keywords: nádorový supresorový protein p53; nádorové buněčné linie; NSG mouse; heterografty; Mice, SCID; ATM protein; Disease Models, Animal; Transplantation, Heterologous; mužské pohlaví; mutace; Chronic lymphocytic leukemia; Mice; Tumor Suppressor Protein p53; Cell Line, Tumor; xenograft model; myši knockoutované; Gene Knockout Techniques; Interleukin Receptor Common gamma Subunit; Lymphoma, Mantle-Cell; Animals; chronická lymfatická leukemie; transplantace heterologní; modely nemocí na zvířatech; ženské pohlaví; Mutation; zvířata; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; biologické markery; myši inbrední NOD; receptory interleukinů - společná gama-podjednotka; Mice, Inbred NOD; Mice, Knockout; myši; Ataxia Telangiectasia Mutated Proteins; myši SCID; Biomarkers; Female; mantle cell lymphoma; Heterografts; lidé; Male; genový knockout; lymfom z plášťových buněk